2007
DOI: 10.1037/0022-006x.75.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarks for psychotherapy efficacy in adult major depression.

Abstract: This study estimates pretreatment-posttreatment effect size benchmarks for the treatment of major depression in adults that may be useful in evaluating psychotherapy effectiveness in clinical practice. Treatment efficacy benchmarks for major depression were derived for 3 different types of outcome measures: the Hamilton Rating Scale for Depression (M. A. Hamilton, 1960A. Hamilton, , 1967, the Beck Depression Inventory (A. T. Beck, 1978;A. T. Beck & R. A. Steer, 1987), and an aggregation of low reactivity-low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
135
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(148 citation statements)
references
References 117 publications
(87 reference statements)
7
135
4
2
Order By: Relevance
“…Previous research suggests that, when individuals suffering from major depressive disorders act as wait-list controls for depression intervention studies, they experience a natural reduction in the severity of depressive symptoms, benchmarking this nontreatment-related reduction at 10% to 15% 47 (Cohen d effect size = 0.37). 38 In the present study, patients were included in the study sample if they showed at least minimal levels of depressive symptoms (BDI of 14 or greater). Comparing the mean pretreatment level of depressive symptoms among participants in our sample (22.0) to a previously established major depressive disorder cut score of 22 46 suggests that approximately half of participants had lower levels of depressive symptoms than [ research report ] those with major depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that, when individuals suffering from major depressive disorders act as wait-list controls for depression intervention studies, they experience a natural reduction in the severity of depressive symptoms, benchmarking this nontreatment-related reduction at 10% to 15% 47 (Cohen d effect size = 0.37). 38 In the present study, patients were included in the study sample if they showed at least minimal levels of depressive symptoms (BDI of 14 or greater). Comparing the mean pretreatment level of depressive symptoms among participants in our sample (22.0) to a previously established major depressive disorder cut score of 22 46 suggests that approximately half of participants had lower levels of depressive symptoms than [ research report ] those with major depression.…”
Section: Discussionmentioning
confidence: 99%
“…Minami and colleagues Minami, Wampold, Serlin, Kircher, & Brown, 2007) provided a more general and formal method of developing benchmarks for routine practice, and applied that method to studies of adult MDD. Their method includes at least three major advances beyond other methods of benchmarking.…”
Section: Benchmarking Routine Psychological Treatment Outcomesmentioning
confidence: 99%
“…However, there are several possible limitations to be considered. For instance, it could be argued that even the most formal method of benchmarking change (Minami et al, 2007) is not a comprehensive method. After all, the amount of change observed is only one portion of the relevant information about the outcome of treatments.…”
Section: Benchmarking Routine Psychological Treatment Outcomesmentioning
confidence: 99%
See 2 more Smart Citations